Do Merkel complexes initiate mechanical itch?. Issue 2 (21st October 2022) - Bataille‐Savattier, Adeline; Le Gall‐Ianotto, Christelle; Lebonvallet, Nicolas; Misery, Laurent; Talagas, Matthieu
Abstract: Itch is a common sensation which is amenable to disabling patients' life under pathological and chronic conditions. Shared assertion easily limits itch to chemical itch, without considering mechanical itch and alloknesis, its pathological counterpart. However, in recent years, our understanding of the mechanical itch pathway, particularly in the central nervous system, has been enhanced. In addition, Merkel complexes, conventionally considered as tactile end organs only responsible for light touch perception due to Piezo2 expressed by both Merkel cells and SA1 Aβ‐fibres ‐ low threshold mechanical receptors (LTMRs) ‐, have recently been identified as modulators of mechanical itch. However, the tactile end organs responsible for initiating mechanical itch remain unexplored. The consensus is that some LTMRs, either SA1 Aβ‐ or A∂‐ and C‐, are cutaneous initiators of mechanical itch, even though they are not self‐sufficient to finely detect and encode light mechanical stimuli into sensory perceptions, which depend on the entire hosting tactile end organ. Consequently, to enlighten our understanding of mechanical itch initiation, this article discusses the opportunity to consider Merkel complexes as potential tactile end organs responsible for initiating mechanical itch, under both healthy and pathological conditions. Their unsuspected modulatory abilities indeed show that they are tuned to detect and encode light mechanical stimuli leading to mechanical itch, especially as they host not only SA1 Aβ‐LTMRs but also A∂‐ and C‐fibres.